PENGARUH TURNOVER INTENTIONS, SELF RATE EMPLOYEE PERFORMANCE, DAN SELF ESTEEM TERHADAP PENERIMAAN DYSFUNCTIONAL BEHAVIOR IN AUDIT DALAM PRESPEKTIF GENDER (Studi padaKantorAkuntanPublik Se- JawaTengah) - Hj. Falikhatun , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
The objective of this research are: first, examining the effect of turnover intentions, self rate employee performance and self esteem on acceptance of dysfunctional behavior in audit, and second tested the differences on acceptance of dysfunctional behavior in audit for male and female auditor Hypotheses that proposed are turnover intentions and self esteem will have positive effect on acceptance of dysfunctional behavior in audit, while, self rate employee performance will has negative effect on acceptance of dysfunctional behavior in audit. The next hypotheses is the difference of acceptance of dysfunctional behavior in audit for male and female auditor. The population is auditors working in public accountant firm located in Central Java. Purposive random sampling used to take the samples. Data collection method that used is mail questionnaires method. Data analyze method is validity and reliability analysis, classic assumption analysis and hypotheses analysis that used multiple regression and independent sample t test. The results are all variables valid and reliable and fulfil classic assumption. The result of hypotheses analysis show that self rate employee performance will has positive significantly effect on acceptance of dysfunctional behavior in audit, while turnover intentions, and self esteem have insignificant positive effect on acceptance dysfunctional behavior. For gender prespective, acceptance of dysfunctional behavior in audit for male and female auditor isn 't different.Keywords: turnover intentions, self rate employee performanc, self esteem, acceptance of dysfunctional behavior in audit, gender.